2018
DOI: 10.1111/1750-3841.14085
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrogen‐Donating or Metal‐Chelating Antioxidants on the Oxidative Stability of Organogels Made of Beeswax and Grapeseed Oil Exposed to Light Irradiation

Abstract: Recently, interest in organogels has increased due to their properties of maintaining a solid state at room temperature and composition of trans-free and highly unsaturated fatty acids. However, the addition of antioxidants is necessary due to the high degree of unsaturation in organogels. The results of this study showed that the addition of sesamol significantly enhanced the oxidative stability of organogels under light irradiation. Therefore, the use of sesamol-supplemented organogels could prolong the shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…One of the most widely studied properties of sesamol is its antioxidant activity. It has been proved to have effective capacity for inhibiting hydroxyl radical-induced deoxyribose degradation and lipid peroxidation , which helps protecting plasma, low-density lipoprotein, and erythrocyte membrane from oxidation. Sesamol also induces nitric oxide (the most important vascular relaxing factor) release from endothelial cells. , It has scavenging effects against hydroxyl (OH • ), superoxide anion (O 2 •– ), nitric oxide, hydrogen peroxide (H 2 O 2 ), and other oxidants, in some cases with an efficiency higher, or equal to those of ascorbic acid and vitamin E . Based on its free radical scavenging activity, it has been suggested to use sesamol in the management of Huntington’s, Alzheimer’s, and Parkinson’s diseases, auto-immunity disorders, and brain damage in autism. …”
Section: Introductionmentioning
confidence: 99%
“…One of the most widely studied properties of sesamol is its antioxidant activity. It has been proved to have effective capacity for inhibiting hydroxyl radical-induced deoxyribose degradation and lipid peroxidation , which helps protecting plasma, low-density lipoprotein, and erythrocyte membrane from oxidation. Sesamol also induces nitric oxide (the most important vascular relaxing factor) release from endothelial cells. , It has scavenging effects against hydroxyl (OH • ), superoxide anion (O 2 •– ), nitric oxide, hydrogen peroxide (H 2 O 2 ), and other oxidants, in some cases with an efficiency higher, or equal to those of ascorbic acid and vitamin E . Based on its free radical scavenging activity, it has been suggested to use sesamol in the management of Huntington’s, Alzheimer’s, and Parkinson’s diseases, auto-immunity disorders, and brain damage in autism. …”
Section: Introductionmentioning
confidence: 99%
“…Hong et al. () found that metal chelators did not show a distinct antioxidant capacity in organogels and the addition of 10 to 40 ppm sesamol significantly enhanced the oxidative stability in beeswax organogels to a greater extent than α‐tocopherol and β‐carotene ( P < 0.05). Sesamol alone showed better oxidative stability than the addition of EDTA or a mixture of sesamol and citric acid (Hong et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…() found that metal chelators did not show a distinct antioxidant capacity in organogels and the addition of 10 to 40 ppm sesamol significantly enhanced the oxidative stability in beeswax organogels to a greater extent than α‐tocopherol and β‐carotene ( P < 0.05). Sesamol alone showed better oxidative stability than the addition of EDTA or a mixture of sesamol and citric acid (Hong et al., ). Sesamol can generate benzoquinone anion radical and sesamolyl radical by UV or pulsed UV laser irradiation in aqueous solution (Nakagawa, ), which could play important roles in strong antioxidant capacities of sesamol in bulk oils and in organogel matrix at UV irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations